Hubungan Antara Kesadaran Kesetaraan Gender pada Mahasiswa dan Sikap Diskriminasi kepada Perempuan - Nur Rofiq Azijah; Ilham Faishal Mahdy (Jurnal Riset Statistika, 2023)
Abstract. Gender equality awareness refers to the awareness of an equal state between men and women in the fulfillment of rights and obligations. Women's participation consists of traditional roles (domestic roles) and transitions (public roles). The purpose of this study is to find out whether there is a relationship between gender awareness in men and discrimination against women. The technique used in sampling is Stratified Random Sampling with a sample count of 100 samples. The method of collecting data is obtained from the distribution of questionnaires in the form of Google forms to respondents. Data processing uses Rank Spearman correlation analysis with the help of the SPSS program. The results showed that there was a linear relationship between the gender equality awareness variable in male students Statistics Unisba and the variable attitude of discrimination in women. This relationship has a positive direction of 0.697 which means the relationship is strong. Based on the results of the study, the increasing awareness of gender equality in male students Statistics Unisba will have to do with increasing understanding of discrimination against women. Abstrak. Kesadaran kesetaraan gender merujuk kepada kesadaran akan suatu keadaan setara antara laki-laki dan perempuan dalam pemenuhan hak dan kewajiban. Partisipasi wanita terdiri dari peran tradisi (peran domestik) dan transisi (peran publik). Tujuan dilakukannya penelitian ini, yaitu untuk mengetahui apakah ada hubungan antara kesadaran kesetaran gender pada laki-laki dan sikap diskriminasi kepada perempuan. Teknik yang digunakan dalam pengambilan sampel adalah Stratified Random Sampling dengan jumlah sampel sebanyak 100 sampel. Metode pengumpulan data diperoleh dari pembagian kuesioner berupa Google form kepada responden. Pengolahan data menggunakan analisis korelasi Rank Spearman dengan bantuan program SPSS. Hasil penelitian menunjukkan terdapat hubungan linier antara variabel kesadaran kesetaraan gender pada mahasiswa laki-laki Statistika Unisba dan variabel sikap diskriminasi pada perempuan. Hubungan ini memiliki arah positif sebesar 0,697 yang berarti hubungannya kuat. Berdasarkan hasil penelitian tersebut, semakin meningkatnya kesadaran kesetaraan gender pada mahasiswa laki-laki Statistika Unisba akan ada hubungannya dengan meningkatnya pemahaman mengenai sikap diskriminasi kepada perempuan.